The Cohesion or Dilation Effect on the Shear Strength of Granitic Residual Soil - Luis J. Andrade Pais; L. M. Ferreira Gomes; Isabel Falorca; Paulo M. Carvalho; Victor P. Cavaleiro (Communications - Scientific letters of the University of Zilina, 2011)
The paper reports laboratory investigations carried out in granitic residual soil from Covilha, to evaluate the stress-strain-dilatancy behaviour to provide a new model. Some soil tests are intended only to classify soil into broad groups. Other tests are done to examine the mechanical behaviour of soils and particularly to investigate their strength and deformation during loading. Drained and undrained triaxial tests were performed to study soil fabric effects on the mechanical behaviour of a granitic residual soil. It was revealed that the dilatancy of the saturated soil contributes to shear stress and strength at lower confining pressures. The cohesion is apparent for small stress and we need to introduce the evaluation of volumetric strain to understand the effect of the dilatancy in the peak strength.